(untitled) (Annals of Medical Research, 2021)
Aim: Sudden sensorineural hearing loss (SSHL) is usually diagnosed in a single ear. The main objective of this study is to assess the dominance of affected ear by comparing right versus left-ear cases.Materials and Methods: We retrospectively examined the records of 105 patients (63 males, 42 females; mean age 41.5±15 years; range 18 to 72 years) between January 2013 and January 2017.Results: Sixty-three of the included cases were male and 42 were female patients. SSHL was diagnosed on the left ear in 51 (48.6%) patients and on the right ear in 49 (45.7%) patients. No statistically significant dominance on the affected ear side was detected whereas bilateral involvement was significantly low. In male patients, 33 (52.3%) had hearing loss on the right and 29 (46%) had hearing loss in the left ear. Sixteen (32.7%) female patients had right ear and 22 (43.1%) had left ear involvement. There was a slight dominance on the right ear in male and on the left ear in female patientsConclusion: There is no significant difference between left and right ear involvement in SSHL. The results of our study which showed right ear dominance in males and left ear dominance in female patients are thought to be purely coincidental.Keywords: Ear, sudden hearing loss, laterality